P552 Anti-TNF Treatment and Risk of Atrial Fibrillation in Inflammatory Bowel Disease Patients. (30th January 2023) - Cohen, Y; Fischman, M; Waterman, M; Dolnikov, K; Azzam, Z S; Ghersin, I
Abstract: Background: Inflammation is thought to play a role in the development of atrial fibrillation (AF). Previous studies suggested that inflammatory bowel disease (IBD) is associated with increased risk of AF. These studies also found IBD patients receiving biologic agents were at higher risk of AF than patients not receiving them. We sought to determine the association between anti-TNF treatment and the risk of AF in IBD patients Methods: In this observational cohort, we included all adult IBD patients who were registered in Rambam Medical Center, diagnosed with IBD from November 1983 to October 2021. We excluded patients who were diagnosed with AF and/or stroke prior to IBD diagnosis. Disease severity was based upon IBD treatment. Mild disease was defined as no treatment, 5-ASA, or topical steroids, while moderate-to-severe disease was defined as any immunomodulator, biologic or systemic steroid therapy. Primary outcome was AF diagnosis. We used Cox proportional hazard model to compare AF in patients receiving anti-TNF treatment to those with mild disease. We further adjusted the hazard ratio of AF development based on known AF risk factors, including age, male gender, cardiovascular disease, chronic kidney disease, pervious venous thromboembolism, hyperlipidemia, diabetes, and thyroid disease. Results: Our initial cohort included 5, 326 patients. After exclusion, 4, 886 patients were included. Median follow-up time was 8.49 years 2, 720 patients were considered as having mild IBD, while 787 patients received anti-TNF medications. During follow-up period, cumulative incidence of AF was 1.50% (n=41) and 0.89% (n=7), respectively (p=0.21). Unadjusted hazard ratio of AF occurrence in anti-TNF patients was 0.6 (95% CI; 0.27-1.3, p=0.211). After adjustment, hazard ratio of AF occurence was 1.33 (95% CI; 0.53-3.3, p=0.545). Conclusion: Anti-TNF treatment was not associated with increased risk of AF among IBD patients. This provides reassurance regarding the cardiovascular safety of anti-TNFs in a real-world IBD cohort.